Adesão de idosos a programa de atividade física em unidade de atenção primária à saúde - Monteiro, Maira Cury [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The current epidemiological scenario confirms the transition patterns of occurrences of diseases in recent decades, a change called epidemiological transition, characterized by decreased occurrence of infectious-contagious diseases and higher chronic non-communicable diseases (NTCDs). In Brazil, they represent about 72% of all deaths in the country. Physical inactivity, together with other behavioral factors, such as the use of tobacco and dietary profile, are responsible for about 80% of the total burden of major chronic diseases. Considering that the Brazilian Centralized Health System (Sistema Único de Saúde) has encompassed and implemented physical activity programs in primary healthcare units, and considering the low adherence of elderly people to these programs, the purpose of this study is to capture from the experience of elderly people the factors that condition their adherence to and dropout from oriented physical activity in the Family Health Strategy. Qualitative research, using forms and non-conducive interview, administered to two groups of individuals: adherence group (AG) and dropout group (DG), with analysis methodology through analysis of thematic type of contents. The results show that elderly people's adherence to or dropout from physical activity programs in primary healthcare units originate from a series of multifactoria aspects as pleasant feeling to the realization exercise, improve health conditions, compliance with recommendations of professionals in health and social life and aspects that stimulate the dropout is sorrow in exercise tolerance, worsening health condition, compliance with contraindication for health professionals, prioritize other daily life activities, negative perception of the conditions of infrastructure related to exercise and fitness difference between program participants. Recommend actions to minimize the withdrawal of the elderly from physical exercise in primary care settings ...

O cenário epidemiológico atual confirma a transição dos padrões de ocorrências de doenças nas últimas décadas, mudança denominada transição epidemiológica, caracterizada pela diminuição da ocorrência de doenças infectocontagiosas, e incremento das doenças crônicas não transmissíveis (DCNT). No Brasil, estas representam cerca de 72% de todas as mortes do país. A inatividade física juntamente com outros fatores comportamentais, como uso de tabaco e perfil alimentar são responsáveis por cerca de 80% da carga total das principais doenças crônicas. Com a abrangência do Sistema Único de Saúde e a implantação de programas de atividade física em unidades de atenção primária à saúde e a baixa adesão de idosos a estes programas o estudo tem como objetivo apreender das experiências dos idosos os condicionantes da adesão e da desistência dos mesmos ao programa de atividade física orientada na Estratégia de Saúde da Família. Pesquisa qualitativa, com a utilização de formulário e entrevista não diretiva, aplicados aos dois grupos de indivíduos: grupo adesão (GA) e grupo desistentes (GD), com a metodologia de análise por análise de conteúdo do tipo temática. Como resultados, ficou evidente que a adesão ou a desistência de idosos a programas de atividade física em unidades de atenção primária à saúde são provenientes de uma série de eventos multifatoriais, corroborando para adesão aspectos como sensação prazerosa com a realização do exercício, melhoria das condições de saúde, cumprimento de recomendações de profissionais da área de saúde e convívio social e para aspectos que estimulam a desistência o desgosto em realizar exercícios, piora da condição de saúde, cumprimento de contraindicação de profissionais de saúde, priorização de outras atividades do dia a dia, percepção negativa das condições de infraestrutura relacionadas ao programa de exercícios e diferença de ...
Adherence of elderly people to physical exercise prograns in primary healthcare unit
Keywords: Cuidados primários de saúde; Idosos; Exercícios físicos para idosos; Programa Saúde da Família (Brasil); Pesquisa qualitativa; Primary health care; Exercise for the aged